Inhibitors of the PLK1 polo-box domain: drug design strategies and therapeutic opportunities in cancer. (2nd January 2023) - Stafford, Jessy M.; Wyatt, Michael D.; McInnes, Campbell
ABSTRACT: Introduction: Polo Like Kinase 1 (PLK1) is a key regulator of mitosis and its overexpression is frequently observed in a wide variety of human cancers, while often being associated with poor survival rates. Therefore, it is considered a potential and attractive target for cancer therapeutic development. The Polo like kinase family is characterized by the presence of a unique C terminal polobox domain (PBD) involved in regulating kinase activity and subcellular localization. Among the two functionally essential, druggable sites with distinct properties that PLK1 offers, targeting the PBD presents an alternative approach for therapeutic development. Areas covered: Significant progress has been made in progressing from the peptidic PBD inhibitors first identified, to peptidomimetic and recently drug-like small molecules. In this review, the rationale for targeting the PBD over the ATP binding site is discussed, along with recent progress, challenges, and outlook. Expert opinion: The PBD has emerged as a viable alternative target for the inhibition of PLK1, and progress has been made in using compounds to elucidate mechanistic aspects of activity regulation and in determining roles of the PBD. Studies have resulted in proof of concept of in vivo efficacy suggesting promise for PBD binders in clinical development.